2023
DOI: 10.1038/s41467-023-39997-y
|View full text |Cite
|
Sign up to set email alerts
|

Topotactic fabrication of transition metal dichalcogenide superconducting nanocircuits

Abstract: Superconducting nanocircuits, which are usually fabricated from superconductor films, are the core of superconducting electronic devices. While emerging transition-metal dichalcogenide superconductors (TMDSCs) with exotic properties show promise for exploiting new superconducting mechanisms and applications, their environmental instability leads to a substantial challenge for the nondestructive preparation of TMDSC nanocircuits. Here, we report a universal strategy to fabricate TMDSC nanopatterns via a topotac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 52 publications
0
1
0
Order By: Relevance
“…Another powerful strategy for seeded growth by patterning precursors is topotactic conversion. 17 During a typical process of topotactic conversion, desired structures such as nanowires and arrays are patterned onto transition metal thin films by electron beam lithography and reactive ion etching (RIE), followed by annealing in chalcogen atmospheres, which topotactically transforms the patterned transition metal into target TMDC nanocircuits (Fig. 3c).…”
Section: Patterned Growth Of 2d Semiconductorsmentioning
confidence: 99%
“…Another powerful strategy for seeded growth by patterning precursors is topotactic conversion. 17 During a typical process of topotactic conversion, desired structures such as nanowires and arrays are patterned onto transition metal thin films by electron beam lithography and reactive ion etching (RIE), followed by annealing in chalcogen atmospheres, which topotactically transforms the patterned transition metal into target TMDC nanocircuits (Fig. 3c).…”
Section: Patterned Growth Of 2d Semiconductorsmentioning
confidence: 99%
“…For example, in 2023, Charaev et al [19] reported an SNSPD produced from BSCCO-layered materials with transition temperatures of up to 25 K, which exceeds the temperature limit of liquid helium. In addition, researchers have conducted preliminary studies on NbSe 2 [20][21][22], a new material that is foreseen to bring about a breakthrough in device performance owing to its unique thermal properties, which is also expected to promote the study of heattransfer mechanisms. Furthermore, transition metal dichalcogenides (TMDCs), such as van der Waals (vdW)-layered materials, are characterized by strong covalent bonds within the layers, which are held together by weak vdW forces between the layers.…”
Section: Introductionmentioning
confidence: 99%